Strategi manajemen dalam risiko likuiditas untuk memperkuat reputasi dan kepercayaan publik pada perbankan syariah - Fauziyah, Tatia Nur (Maliki Interdisciplinary Journal, 2025)
Liquidity risk management is a strategic component in maintaining the resilience, reputation, and public trust in Islamic banking. Liquidity risks that are not properly managed can lead to financial instability and lower the credibility of the institution. This research aims to analyze the liquidity risk management strategies applied by Islamic banks in strengthening their reputations and maintaining public trust. Through a qualitative approach based on literature studies from various national and international journals, it was found that effective strategies include strengthening governance through the supervision of the Sharia Supervisory Board (DPS), diversifying sharia-based liquidity instruments, optimizing the role of asset and liability committees (ALCOs), and increasing transparency of financial information. These strategies form public trust because they demonstrate professionalism, sharia compliance, and measurable financial stability. Thus, the implementation of comprehensive liquidity risk management not only maintains the financial health of Islamic banks, but also strengthens the public's reputation and confidence in the reliability of the Islamic financial system.